Dendritic silica@aqueous miscible organic-layered double hydroxide hybrids. Issue 46 (7th November 2018) - Suo, Hongri; Chen, Chunping; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : We present the synthesis of a series of dendritic hierarchical hybrid SiO2 @AMO-LDHs with tuneable properties suitable for a wide range of applications. Abstract : We present the synthesis of a series of hierarchical Silica@Layered Double Hydroxide (SiO2 @LDH) core@shell hybrid materials that have been post-treated using the Aqueous Miscible Organic Solvent Treatment (AMOST) method. The Silica@Aqueous Miscible Organic-Layered Double Hydroxide (SiO2 @AMO-LDH) hybrids exhibit composition flexibility with radially oriented AMO-Mg y Al-CO3 -LDH nanosheets resulting in a new dendritic morphology.